2020
DOI: 10.1007/s00038-020-01390-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive symptoms and comorbidities for severe COVID-19 and intensive care unit admission: a systematic review and meta-analysis

Abstract: Objectives COVID-19 has a varied clinical presentation. Elderly patients with comorbidities are more vulnerable to severe disease. This study identifies specific symptoms and comorbidities predicting severe COVID-19 and intensive care unit (ICU) admission. Methods A literature search identified studies indexed in MEDLINE, EMBASE and Global Health before 5th March 2020. Two reviewers independently screened the literature and extracted data. Quality appraisal was performed using STROBE criteria. Random effects m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
278
7
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(382 citation statements)
references
References 22 publications
36
278
7
20
Order By: Relevance
“…Five recent meta-analyses (two as yet only available on preprint websites) have assessed the prevalence of co-morbidities in people with COVID-19. 9,10,[47][48][49] Three systematic reviews, with search dates finishing between the end of February and 5 March 2020, found similar results to those reported here, but with fewer studies. 9,10,49 Emami et al, 9 Li et al 49 and Yang et al 10 included 10, six and nine studies, respectively, and in COVID-19 patients reported a prevalence of T A B L E 2 Summary of meta-analyses results for prevalance of co-morbidities, and increased risk of mortality and severity of disease by comorbidities, in COVID-19 patients hypertension of 16%-17.1%, diabetes 8%-9.7%, and CVD 5%-12%.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Five recent meta-analyses (two as yet only available on preprint websites) have assessed the prevalence of co-morbidities in people with COVID-19. 9,10,[47][48][49] Three systematic reviews, with search dates finishing between the end of February and 5 March 2020, found similar results to those reported here, but with fewer studies. 9,10,49 Emami et al, 9 Li et al 49 and Yang et al 10 included 10, six and nine studies, respectively, and in COVID-19 patients reported a prevalence of T A B L E 2 Summary of meta-analyses results for prevalance of co-morbidities, and increased risk of mortality and severity of disease by comorbidities, in COVID-19 patients hypertension of 16%-17.1%, diabetes 8%-9.7%, and CVD 5%-12%.…”
Section: Discussionsupporting
confidence: 79%
“…These results are complementary to those reported here, which is unsurprising given that these reviews cover many of the same studies, although the results presented here are based on more data (from 13 or 14 studies), with greater care taken to remove those cohorts which overlap from the review. Jain and Yuan 48 identified seven studies NOTE: Weights are from random effects analysis .…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors that have been identified in prior studies include older age, male sex, hypertension, diabetes, chronic obstructive pulmonary disease, cardiac disease, liver disease, chronic kidney disease, neurologic disorders, cancer, obesity, higher overall burden of comorbidity, and smoking. 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors for developing severe COVID-19 disease have been reported, including sociodemographic factors and comorbid conditions. 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 However, most prior studies, particularly those published earlier in the course of the pandemic, did not include multivariable adjustment to identify independent risk factors, and few studies examined a range of different disease outcomes, including hospitalization, mechanical ventilation, and death. Most prior studies have been local or regional, rather than national, in scope.…”
Section: Introductionmentioning
confidence: 99%
“…This is the most comprehensive systematic review and meta-analysis of COVID-19 ICU cases and outcomes to date to our knowledge. Many reviews explored COVID-19 prognosis, with some reporting generally on all [36] or hospitalized cases [37], or from a certain region [38], or focused on speci c aspects such as mortality [39] or outcomes [40], with only one systematic review speci cally addressing IMV mortality [41]. Here we attempt to provide a comprehensive assessment of ICU-admitted COVID-19 patient characteristics, regional discrepancies, as well as overall ICU and IMV speci c outcomes and their associated factors.…”
Section: Discussionmentioning
confidence: 99%